Governance Challenges on Food Loss and Waste (FLW) Reduction in Indonesia - Sidik Pramono; Sarah Anggraeni Suhartono (Jayapangus Press, 2026)
Indonesia’s commitment to reducing food loss and waste (FLW) is hindered by a governance gap that transforms a technical issue into a structural one. This study analyses the systemic barriers within Indonesia's regulatory framework through a public administration and governance lens. The findings of this research reveal that institutional fragmentation remains the core obstacle, with silo effect among agencies resulting in weak cross-sectoral coordination. This lack of integration leads to inconsistent data and misalignment between central and regional governments, as well as disconnection from non-state actors. Ultimately, FLW reduction in Indonesia cannot be solved by isolated technical fixes. It requires a collaborative governance transformation that synchronizes authority and integrates policy execution across the food system chain.